Saúde, participação e controle social: lutas e ações estratégicas do Mops/SE pela efetivação dos direitos à saúde em Aracaju/SE (1989-2008) - Santos, Rosângela Marques dos (2009)
This research presents an analysis of the struggles and strategic actions developed by the Movement Popular for Health in Sergipe Mops/SE in the period 1989/2008. The object of study highlighted the participation and social control aiming at the realization of rights to health. It appeared in Aracaju in the 1980 Mops/SE in the figure since then socio-political scenario with the work of building and strengthening of actions for the development of a social policy of public health and quality. To do so, acts in connection with the Popular Education and invests in training its militant policy of bringing articulate scientific knowledge and popular knowledge in order to recover and popular cultural practices. The theoretical frameworks used for the analysis of interviews and testimony were based on Gramscian and the privileged categories in the study were social movements, participation and social control. Qualitative research took place from bibliographical an documentary research, enriched with empirical observations during the course of events. She has produced a video documentary entitled Mops/SE 20 Years Expanding Achievements , this feature can be used with educational purposes, in addition to being an instrument to contribute to the historical memory of the movement. The study about the struggles and strategic actions of Mops/SE it highlighted the defense of a political project in a wider perspective of health and its contribution to expand the political space for the exercise of participation and social control and the struggles to build democratic processes participation and confrontation of social contradictions are given in the struggles between different political forces in which collective interests are not always included as a priority in government agendas